2011
DOI: 10.3945/ajcn.110.003251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meals rich in either monounsaturated or saturated fat on lipid concentrations and on insulin secretion and action in subjects with high fasting triglyceride concentrations

Abstract: Background: The nature of dietary fats and fasting concentrations of triglycerides affect postprandial hypertriglyceridemia and glucose homeostasis. Objectives: The objectives were to examine the effects of meals enriched in monounsaturated fatty acids (MUFAs) or saturated fatty acids (SFAs) on postprandial lipid, glucose, and insulin concentrations and to examine the extent of b cell function and insulin sensitivity in subjects with high fasting triglyceride concentrations. Design: Fourteen men with fasting h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 24 publications
(32 reference statements)
3
77
0
3
Order By: Relevance
“…42,43 In subjects with high fasting triglyceride concentrations, a high MUFA meal causes a lower postprandial rise of insulin that a meal high in saturated fatty acids. 44 According to this data, our results show a lower elevation of post-OGTT insulin levels in subjects consuming only olive oil, while the highest elevation was observed in subjects who consume sunflower oil exclusively.…”
Section: Discussionmentioning
confidence: 61%
“…42,43 In subjects with high fasting triglyceride concentrations, a high MUFA meal causes a lower postprandial rise of insulin that a meal high in saturated fatty acids. 44 According to this data, our results show a lower elevation of post-OGTT insulin levels in subjects consuming only olive oil, while the highest elevation was observed in subjects who consume sunflower oil exclusively.…”
Section: Discussionmentioning
confidence: 61%
“…The most effective replacement for SFAs in terms of risk factor outcomes for CVD is the monounsaturated fatty acids (MUFAs), and the polyunsaturated fatty acids (PUFAs) but 4 in much less importance [13]. In accordance, recent studies have demonstrated that olive oil, which is the only natural and most relevant source of MUFAs in the diet, when compared with butter, can postprandially limit TG excursions and buffer the pancreatic β-cell hyperactivity and peripheral insulin intolerance in subjects with normal [14] and high fasting [15] TG levels.…”
Section: Introductionmentioning
confidence: 99%
“…Higher-weight subjects benefit more from the consumption of MUFA (olive oil) rather than PUFA (walnut) or SFA (butter) (45). Also, olive oil reduced PPL in men with fasting hypertriglyceridemia (42) and in overweight subjects with type 2 diabetes (83). Increases in postprandial insulin sensitivity after MUFA intake may increase LPL activity and therefore TAG clearance.…”
Section: Amount and Type Of Fatmentioning
confidence: 99%
“…However, the degree of PPL depends on the type of fat ingested. Compared with butter (high in SFA), olive oil (high in MUFA) produced similar (6,38,60,81) or greater (38,56) or lower (42,43,82) PPL in healthy populations. Mixed results were also found when comparing olive oil with other fats and oils rich in SFA (palm oil or palm olein oil or cocoa butter), or PUFA (walnuts, corn oil, salmon oil, flaxseed oil, safflower oil, or sunflower oil), or MUFA (rapeseed oil or high oleic sunflower oil).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%